2018
DOI: 10.1002/lary.27257
|View full text |Cite
|
Sign up to set email alerts
|

Current practices in microvascular reconstruction in otolaryngology–head and neck surgery

Abstract: NA Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…In situations where the defect has been deemed to be borderline and there is low risk of communication with the neck wound, for example, a partial glossectomy defect, another option could be skin graft reconstruction, primary closure or delayed healing. When free tissue transfer reconstruction is needed, a two‐team approach with simultaneous starts can lead to decreased operative time, and anesthesia time, while also allowing each team to focus on a particular element of the case 25 . This appears to be the case in the United States where 98.5% of programs report a two‐team approach at least some of the time, and has been widely adopted in 82% of hospitals in the United Kingdom 25,26 …”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…In situations where the defect has been deemed to be borderline and there is low risk of communication with the neck wound, for example, a partial glossectomy defect, another option could be skin graft reconstruction, primary closure or delayed healing. When free tissue transfer reconstruction is needed, a two‐team approach with simultaneous starts can lead to decreased operative time, and anesthesia time, while also allowing each team to focus on a particular element of the case 25 . This appears to be the case in the United States where 98.5% of programs report a two‐team approach at least some of the time, and has been widely adopted in 82% of hospitals in the United Kingdom 25,26 …”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…Pedicled locoregional flaps were the first workhorse flaps for reconstructing head and neck defects [1][2][3] , but have largely been replaced by free flaps. As our understanding of surgical and anatomic considerations improves, microvascular free tissue transfer has become the gold standard for reconstruction with success rates around 95% [4][5][6][7][8] . However, there are many situations where pedicled locoregional flaps still have merit.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of otolaryngologists who perform microsurgical reconstruction surprisingly showed that almost double the proportion of surgeons will perform the entire ablation and reconstruction by themselves as opposed utilizing the two-team approach with a surgeon outside their specialty. 15 It is unclear if this is due to necessity or preference; however, further research should investigate what prohibits and allows us to work together effectively, as well as how collaboration, or lack thereof, affects research and patient care.…”
Section: Discussionmentioning
confidence: 99%